Analisis Sistem Pengawasan Point Of Sales (Pos) Terhadap Penerimaan Pajak Hotel Pada Badan Pendapatan Daerah Kabupaten Mimika - Yoane Vianney; Abu Bakar (Journal of Economics and Regional Science, 2023)
This study aims to determine the effectiveness of the Point Of Sales (POS) monitoring system to increase hotel tax revenue at the Regional Revenue Agency of Mimika Regency. The research method used in this research is descriptive research method. Data collection techniques used are observation, documentation, and interview techniques. The data analysis carried out in this study was qualitative data analysis, where in the data analysis process, triangulation techniques were used. The results of this study indicate that the application of a Point Of Sales (POS) monitoring system to increase hotel tax revenue at the Regional Revenue Agency of Mimika Regency has not been effective. This is because there are still taxpayers who use handwritten receipts as proof of payment for hotel room orders by customers, and do not use the results of a printed bill from the Point of Sales (POS) system